Phylogenomics and multigene phylogenies decipher two new cryptic marine algae from California, Gelidium gabrielsonii and G. kathyanniae (Gelidiales, Rhodophyta) - Boo, Ga Hun (Journal of phycology, 2019)
© 2018 Phycological Society of America.